Teacher Performance and Principal Leadership Patterns - Ucup Supriatna (International Journal of English and Applied Linguistics (IJEAL), 2021)
The value of effective management in educational organizations is increasingly recognized by various stakeholders. The purpose of this study is to find out if the Head of Islamic Religious Education in Ketapang City uses an effective leadership pattern in managing his leadership. The findings of this study show that madrasah Aliyah level principals are effective leaders who understand how to be professional leaders. Professionally, this means that the head of Aliyah madrasa has established himself as an education leader and is committed to maintaining high standards at all times. In some cases, the head of Madrasah Aliyah falls into the category of master school leaders who are able to show quality in areas where others can place the principal. as a school leadership authority. The principal is not only good-looking, but also able to show an understanding of the concept of quality. However, no correlation was observed between the principal's leadership and student achievement levels. This indicates that the principal is an education leader with a professional or even a master's degree, but there is no relationship between leadership level and student learning achievement.